ISLAMIC DEVELOPMENT IN THAILAND - Bueto, Niarmeen; Saprudin, Saprudin (Universitas Suryakancana, 2024)
Islam in Thailand in Pattani and other southern Thailand regions. The entry of Muslim workers from Malaysia and Indonesia into Thailand is one of the causes of the development of Islam in Thailand. The aim of this study is to describe the development of Islam in Thailand and religious freedom in Thailand. The method used in this study is the method of social relations with data sources of the results of observation of the development of Islam in Thailand. The results of this study were found Thailand is one of the Southeast Asian nations where Buddhism is practiced by the majority of the population. But in Thailand, there is a region called Southern Thailand that has a large Muslim population. In Pattani and a few other provinces, specifically. Islam was brought to Thailand through Arab trade. Ancient Thai paintings of the Arabs in the Ayuthaya region and the Arabs' success in founding Daulah Islamiyah provide as evidence for this. Despite being a minority religion in Thailand, Islam nonetheless maintains a significant presence there because to the Patani United Liberation Organization (PULO)